Pengaruh Pengadaan Barang dan Jasa pada Masa Pandemi Corona Virus Disease 2019 (COVID-19) Terhadap Kondisi Keuangan Rumah Sakit di RSUP Dr. Kariadi Semarang - Sasongko, Himawan (Jurnal Ekonomi Kesehatan Indonesia, 2021)
The mechanism for procuring goods and services in handling emergencies is different from regular/ordinary conditions. The main difference is in the stage of the procurement implementation. Today's problems are the enormous price disparity, the increasing availability and demand, especially for personal protective equipment (PPE). The disparity has resulted in more significant expenses in hospital spending, this condition impact hospital finances. This research is an observational study. The method is qualitative with interviews and data collection. The data taken are primary data and secondary data. Informants consist of main informants and triangulation informants. The data collection instrument was an in-depth interview guide. From the research results obtained: before the COVID-19 pandemic, two methods of implementing procurement (E-Catalogue and Direct Procurement) while procurement during the pandemic used three methods (E-Catalogue, Direct Procurement and Direct Appointment). The procurement process is following the established rules. The procurement process that is carried out has complied with the procurement principles and ethics. There has been a change in the General Procurement Plan for 2020 due to the pandemic. The realization of revenue for Dr Kariadi Hospital in 2020 exceeded the predetermined target, so it can be said that the financial condition of Dr Kariadi Hospital during the COVID-19 pandemic was considered healthy. This study concludes that the procurement process in the COVID-19 pandemic condition follows the principles, ethics and regulations that have been set, as well as the financial condition of Dr Kariadi during the COVID-19 pandemic, was considered healthy.